1993
DOI: 10.1007/bf00005416
|View full text |Cite
|
Sign up to set email alerts
|

The consortium of the sponge Lubomirskia baicalensis in Lake Baikal, East Siberia

Abstract: The spatial distribution of the fauna associated with a branched sponge, Lubomirskia baicalensis, endemic of Lake Baikal has been quantitatively studied. The biomass and numbers of three amphipod species which inhabit the sponge correlate (linearly or non-linearly) with the weight of the sponge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 3 publications
1
8
0
1
Order By: Relevance
“…Brandtia parasitica has a spatial distribution that includes the entire shoreline of Lake Baikal, from 1.5 to 60 m depth, rarely down to 200 m. Its presence is strongly correlated with that of the Baikalean freshwater sponge, Lubomirskia baikalensis which it inhabits. Some researchers believe it is parasitic, feeding on the sponge's body tissues (Kamaltynov et al, 1993;Dembitsky et al, 1994), others think it is merely commensal with the sponge (Timoshkin, 2000;Mekhanikova, 2001). The other two amphipods have distributional characteristics close to that of B. parasitica.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Brandtia parasitica has a spatial distribution that includes the entire shoreline of Lake Baikal, from 1.5 to 60 m depth, rarely down to 200 m. Its presence is strongly correlated with that of the Baikalean freshwater sponge, Lubomirskia baikalensis which it inhabits. Some researchers believe it is parasitic, feeding on the sponge's body tissues (Kamaltynov et al, 1993;Dembitsky et al, 1994), others think it is merely commensal with the sponge (Timoshkin, 2000;Mekhanikova, 2001). The other two amphipods have distributional characteristics close to that of B. parasitica.…”
Section: Resultsmentioning
confidence: 97%
“…All species studied are known to have seasonal migration activity. Kamaltynov et al (1993) described downward migrations of adult B. parasitica in the autumn, at a time when the winds increase. They believed the migrations serve as a mechanism to avoid wave action.…”
Section: Resultsmentioning
confidence: 97%
“…This term was introduced to biocenology by Beklemishev (1951) and Ramenskii (1952). Although the volume and content of the notion of consortia remain controversial (Arnol'di et al , 1969;Rabotnov, 1969Rabotnov, , 1973Rabotnov, , 1974Nosova, 1973;Voronov, 1974;Kamaltynov et al , 1993), we believe that it fits best for elementary biocenosis which includes interacting populations of the edificator and consort species. As for aquatic ecosystems, we consider the viewpoint of Kharchenko and Protasov (1981) as the most convincing.…”
Section: Introductionmentioning
confidence: 94%
“…Interestingly, however, in a reference sponge sample from the River Pilica (of which the River Gac is a tributary), the same authors identified Marionina riparia. To the best of our knowledge, the only previous record of oligochaetes associated with lake-dwelling sponges included members of Naididae, Propappidae, Lumbriculidae and Tubificidae found on the basal surface and in cavities between the substrate and the base of Lubomirskia baicalensis (PALLAS, 1773) (Demospongiae: Haplosclerida: Spongillina: Lubomirskiidae), a shallow-water (4 -15 m) endemic of Lake Baikal (KAMALTYNOV et al, 1993).…”
Section: Ecologymentioning
confidence: 99%